Perlindungan Hukum terhadap Harta Pusaka Tinggi Minangkabau dari Perbuatan Melawan Hukum dalam Pensertifikatan Tanah (Studi Putusan Mahkamah Agung Nomor 219 K/Pdt/2025) - Valentinus Andri Ginting; Rosnidar Sembiring; Maria (Jurnal Hukum Lex Generalis, 2025)
High ancestral property (harta pusaka tinggi) in Minangkabau is a communal right inherited matrilineally and, in principle, may not be transferred individually, which makes it highly vulnerable when land registration is conducted in a distorted manner. The research method employed is normative juridical research. The results show, that unlawful acts in the registration of high ancestral property are reflected in land registration carried out by parties not authorized as mamak kepala waris, the falsification or manipulation of genealogical records (ranji) and customary documents, and the disregard of the principle of “bulek kato dek mufakaik” (decision by consensus) in decision-making over clan land. legal protection of high ancestral property operates on multiple layers through customary mechanisms and national legal instruments, including the recognition of communal rights in the 1945 Constitution and the Basic Agrarian Law, land registration regulations, and civil lawsuits against defective land certificates.